Development and validation of genome-wide polymorphic InDel marker set for harnessing the CC-genome wild rice species in the genus Oryza - Lopez, Patricia Izabelle M.; Hechanova, Sherry Lou; Li, Charng-Pei; Cohrs, Sam; Choi, Il-Ryong; Cruz, Pompe C. Sta.; Hernandez, Jose E.; Laude, Tonette P.; Kim, Sung-Ryul (Frontiers in Plant Science, 2026)
Wild rice species serve as a valuable genetic reservoir for rice improvement, and the DNA segments containing useful genes/alleles can be transferred to elite rice varieties through crosses. However, DNA markers, which are essential tools for genetic analysis and molecular breeding, are not yet well-established for harnessing wild rice species. To enable an efficient utilization of the CC-genome wild rice species in the genus Oryza, we developed a genome-wide polymorphic InDel marker (≥20 bp) set comprising 182 markers through positional sequence alignments between O. officinalis (CC-genome) and rice cultivars (AA-genome). These markers were evenly distributed across the 12 chromosomes, with ~2Mb marker intervals. For validation of marker polymorphism, all the markers were tested by using PCR-agarose gel analysis with 12 accessions of CC-genome species (four accessions each from O. eichingeri, O. officinalis, and O. rhizomatis), two accessions of BBCC-genome species (O. minuta), and two cultivars, Nipponbare (japonica) and IR24 (indica). Out of 182 markers, 172 markers (94.5%) successfully amplified and exhibited polymorphism between rice and the CC-genome accessions, corresponding to an average marker interval of ~2.17Mb across the rice genome. Moreover, the marker set also showed high polymorphism (84.1-92.9%) when applied to BBCC-genome species. Based on the marker validation data, five markers were selected for species identification within the three CC-genome species. In addition, the polymorphic markers successfully detected wild rice introgressions from the wide hybridization progenies. The newly developed marker set will function as valuable genomic tools for harnessing CC-genome and CC-genome containing germplasm for rice improvement.